The roles of extracellular matrix proteins, apoptosis and c-kit positive cells in the pathogenesis of ureteropelvic junction obstruction - Ozel, S. K.; Emir, H.; Dervisoglu, S.; Akpolat, N.; Senel, B.; Kazez, A.; Buyukunal, S. N. C. (Elsevier Sci Ltd, 2010)
Aim: To investigate histopathological changes in ureteropelvic junction obstruction (UPJO) from an etiological perspective. Patients and methods: Medical records of patients with UPJO were reviewed and pathological specimens collected. Nephrectomy materials from forensic autopsies were taken as controls. Specimens were assessed with light microscopy. Fibronectin, type 4 collagen, laminin, Bax and Bcl-2 expression for apoptosis, together with interstitial cells of Cajal determination with c-kit were determined immunohistochemically. Staining scores were evaluated semiquantitatively. Results were evaluated using Mann-Whitney U-test. Results: Control group comprised 14 children (median age, 3.5 years; 6 months-17 years). Study group comprised 22 children with UPJO (median age, 9 months; 1 month-10 years). Light microscopy revealed non-specific inflammation, epithelial proliferation and atrophy with fibrosis in the smooth muscle of the UPJ in all patients. Fibronectin, type 4 collagen and laminin were found to be significantly increased in UPJO at the intrafascicular space of smooth muscle and the matrix of stroma. Bcl-2 expression was increased in UPJO. c-Kit was unable to stain interstitial cells of Cajal, but staining for mast cells was significant. Conclusions: High expression of fibronectin, laminin and type 4 collagen may indicate a relation to the pathogenesis of UPJO. Defective kidney morphogenesis, during branching and tubulogenesis of ureteric bud, may be responsible for this congenital pathology. (C) 2009 Journal of Pediatric Urology Company. Published by Elsevier Ltd. All rights reserved.
Keywords: Fibronectin; Extracellular matrix proteins; Ureteropelvic junction obstruction; Etiology